Features of construction in ukraine SROs - Vakhovych, I. (Ways to Improve Construction Efficiency, 2015)
The features of the self-regulation in construction in Ukraine. We have positive experience of winder. The recommendations on the direction of improvement of the activity of self-regulatory organizations in construction.